Physiotherapy after episiotomy for vaginal birth - Agata Wawryków; Katarzyn Korabiusz; Monika Stecko; Anna Fabian - Danielewska; Agnieszka Wilczyńska; Mirela Niedzielska; Inga Janik; Martyna Maciejewska; Andrzej Torbe` (Kazimierz Wielki University, 2018)
Episiotomy is one of the most frequently performed procedures in obstetrics. Since the 21st Century it became a standard procedure performed on the delivery ward. The latest recommendations of the Polish Gynecological Society Expert Committee recommend abandoning the routine groin incision, while in justified cases it indicates the use of mid-lateral incision. Crotch incision increases the risk of many labor problems both early and late. In order to reduce the risk of complications after episiotomy, early improvement is recommended. Physiotheraphy helps to reduce pain, it has anti-edema effect and improves the overall functional status of the woman in labor.